Colored memories [ a biographer's quest for the elusive Lester A. Walton - Curtis, Susan , 1956- (University of Missouri Press, 2008)
"Explores the life of African American Lester A. Walton whose illustrious career spanned the first six decades of the twentieth century but who is now forgotten. Curtis explores the failure of collective memory and America's obsession with race as she discovered Walton and his place in history"--Provided by publisher